Apusomonad rhodopsins: A new family of ultraviolet to blue light–absorbing rhodopsin channels - Luis Javier Galindo; Shunki Takaramoto; Takashi Nagata; Andrey Rozenberg; Hiroto Takahashi; Oded Béjà; Keiichi Inoue (Proceedings of the National Academy of Sciences, 2025)
Apusomonads are sediment-dwelling bacterivorous protists that are sister to all Opisthokonta. They have been found to show a negative phototactic response to blue light, mediated by an as-yet unidentified photoreceptive system. Here, by screening available apusomonad omics data we found genes of a distinct group of microbial rhodopsins, apusomonad rhodopsins (ApuRs). ApuRs, heterologously expressed in mammalian cells, absorbed near-UV or violet light, suggesting that ApuRs could be involved in apusomonads’ photoavoidance response toward short-wavelength light. Electrophysiological measurements indicate that ApuRs are anion-selective rhodopsin channels which evolved independently of the family of channelrhodopsins widespread in other unicellular eukaryotes. In ApuRs, channel opening is triggered by photoisomerization of the retinal from its all- trans form to 13- cis and 11- cis forms. We found that intracellular proton transfer is involved in channel opening and determines the channel’s open/close kinetics. These findings expand our understanding of the photobiology of heterotrophic flagellates and demonstrate that UV-absorbing ApuRs are in fact the most blue-shifted rhodopsin channels known to date.